Zambia: Agricultural Marketing Information Centre (AMIC) - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2002)
The Agricultural Marketing Information Centre (AMIC) was created in the early 1990s following the demise of the national agricultural marketing board and price controls on agricultural inputs, produce and other commodities.